2021
DOI: 10.1111/edt.12706
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between periapical radiography and cone beam computed tomography for the diagnosis of anterior maxillary trauma in children and adolescents

Abstract: Background/Aims: Under-estimating the damage caused by trauma to the dental structures may delay treatment. Timely and accurate diagnosis remains challenging in clinical practice. Radiography is an important modality for the diagnosis of traumatic injuries. The aim of this study was to compare the efficacy of periapical radiography and cone beam computed tomography for the diagnosis of trauma to the anterior maxillary dentoalveolar region in children and adolescents. Material and methods: Images of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…This study showed that the use of CBCT without specific training did not improve the overall diagnostic performance of paediatric dentists in case of TDIs, despite the fact that CBCT is becoming a commonly used diagnostic imaging tool in dentistry. This is not in accordance with reports describing that CBCT provided superior interpretation of information with a better insight into diagnostic dilemmas and complex treatment decisions [ 28 31 ]. However, it should be emphasized that in these studies observers were specialists in endodontics or in oral maxillofacial radiology, all of them better trained in CBCT reading.…”
Section: Discussioncontrasting
confidence: 85%
“…This study showed that the use of CBCT without specific training did not improve the overall diagnostic performance of paediatric dentists in case of TDIs, despite the fact that CBCT is becoming a commonly used diagnostic imaging tool in dentistry. This is not in accordance with reports describing that CBCT provided superior interpretation of information with a better insight into diagnostic dilemmas and complex treatment decisions [ 28 31 ]. However, it should be emphasized that in these studies observers were specialists in endodontics or in oral maxillofacial radiology, all of them better trained in CBCT reading.…”
Section: Discussioncontrasting
confidence: 85%
“…Cone-beam computed tomography is a revolutionary diagnostic tool that has proven superior to periapical radiographs for visualizing pulp canal configuration [19,20]. The features of CBCT that advocate its use for endodontic investigation include higher resolution, increased accuracy, three-dimensional imaging of the teeth, elimination of overlaps, earlier detection of apical lesions, and 3-D reconstruction of root canal systems [20][21][22][23][24][25][26]. In a joint position statement, the American Association of Endodontists (AAE) and American Academy of Oral and Maxillofacial Radiology (AAOMR) recommend the use of limited field-of-view CBCT for endodontic evaluation of teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported CBCT exhibited greater sensitivity for the diagnosis of lateral luxations, alveolar cortical plate fractures, transverse root fractures, and tooth resorption. 106,107 However, in both studies the examiners were only provided with radiographs and/ or CBCT without any accompanying clinical information. The results may therefore not reflect the use of CBCT for trauma diagnosis in a clinical setting where the availability of other information may make it possible to accurately diagnose without a CBCT scan.…”
Section: Endodontic Surgerymentioning
confidence: 99%